Formation of Personal Capabilities in the Undergraduate Teacher Training Formation of Personal Capabilities in the Undergraduate Teacher Training - Katarina Mackova (Communications - Scientific letters of the University of Zilina, 2014)
In the paper the author deals with her experience with the realization of the interventiontraining program focused on the self-development related to the personality competencies in the professional preparation of teachers. It points out the efficiency of the experiential forms of education from the point of view of their personal corrective action. To verify the efficiency of the realized program, the Kirpatrick´s evaluation model is applied here.